Printing silver paste for touch screen and preparation method thereof

Printed silver paste prepared by using raw materials such as silver powder, conductive fillers and modified polyurethane resins, the problems of high cost, insufficient adhesion and high-temperature conductive stability of traditional silver paste are solved, and lower-cost and high-performance touch screen silver paste is achieved. .

CN119480209AActive Publication Date: 2025-02-18DONGGUAN DOMAL ELECTRONICS SCI & TECH

Patent Information

Application Number
CN202411586929.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The high silver powder content in traditional touch screen silver paste leads to high production costs and insufficient adhesion and high-temperature conductive stability, which limits its application prospects.

Method used

Printed silver paste is prepared using silver powder, conductive filler (made from MXene nanosheets and Ag composite materials) and modified polyurethane resin. The viscosity is reduced by modifying silicone in polyurethane resin, and the fluidity is improved. The MXene nanosheets are used to reduce the viscosity and improve fluidity. The high specific surface area and sheet structure enhance the conductivity and mechanical strength.

Benefits of technology

The amount of silver powder is used, the production cost is reduced, the conductive properties, adhesion and thermal stability of silver paste are improved, and its performance under high temperature conditions is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of touch screens, and discloses printing silver paste for a touch screen and a preparation method of the printing silver paste. The prepared silver paste is prepared from silver powder, conductive filler, modified polyurethane resin and an organic solvent as raw materials. Wherein the silver powder and the conductive filler serve as conductive phases, so that the substrate has excellent conductive performance, the hardness, the adhesive force and the thermal stability of the cured silver paste are improved, the use amount of the silver powder is reduced, and the production cost is reduced; and organic silicon is introduced into the modified polyurethane resin, so that the viscosity of polyurethane is reduced, the flowability of the silver paste is improved, and the silver paste is easy to manufacture and process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of touch screens, and in particular to a printing silver paste for touch screens and a preparation method thereof. Background Art

[0002] Touch screens are an indispensable part of electronic products, and their preparation process plays a key role. As a key conductive material in touch screens, silver paste for touch screens, with its unique performance advantages, brings unprecedented sensitivity and stability to touch screens. During the manufacturing process of touch screens, silver paste for touch screens is evenly coated on the surface of the screen through a precise printing process to form fine conductive lines. These lines, like neural networks, accurately transmit touch signals to the processor, thereby realizing the touch function of the screen. The high conductivity of silver paste for touch screens ensures fast and accurate signal transmission, greatly improving the response speed and sensitivity of the touch screen.

[0003] Traditional silver pastes mostly use a high content of silver powder as the conductive phase, but the high cost of silver and the decreasing silver ore resources have largely restricted the application prospects of silver pastes for touch screens. Therefore, conductive fillers with lower costs but better conductivity are needed to replace part of the silver powder and reduce production costs. In addition, considering the application of silver pastes for touch screens, it is also necessary to improve the adhesion of silver pastes and the stability of conductivity at high temperatures. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a printing silver paste for a touch screen and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A printing silver paste for a touch screen comprises the following raw materials in parts by weight: 45-65 parts of silver powder, 10-20 parts of conductive filler, 8-15 parts of modified polyurethane resin, and 20-30 parts of organic solvent; The organic solvent is one or two of butyl butyrate, diethyl glutarate and tributyl citrate; The conductive filler is prepared by the following steps: Step A1, add 40% hydrofluoric acid (w / v) to Ti3AlC2 powder, stir in a water bath at 30-40°C for 8-10 hours, filter and wash until the pH of the filtrate is 6-7, then dry the filter cake, stir in dimethyl sulfoxide for 8-12 hours, centrifuge, wash, redisperse in deionized water for ultrasonic treatment for 3-5 hours, centrifuge, and freeze-dry to obtain MXene nanosheets; Step A2, disperse the MXene nanosheets evenly in deionized water, add 2 / 3 of the mass of sodium hydroxide and stir for 1.5-2.5 hours, then add chloroacetic acid and the remaining sodium hydroxide, heat to 55-65°C and stir for 2-4 hours, wash to neutrality, and dry to obtain carboxylated MXene nanosheets; Step A3, disperse the carboxylated MXene nanosheets evenly in N,N-dimethylformamide (DMF), slowly drop the silver nitrate DMF solution, stir evenly, adjust the pH of the system to 10-11, then add 80wt% hydrazine hydrate, react at 35-45°C for 30-50min, filter, wash, redisperse in ethanol and stir for 1-2h, filter, and dry to obtain a MXene / Ag composite material; Step A4, dispersing the MXene / Ag composite material in a mixture of 0.5 mol / L Tris-HCl buffer solution with a pH of 8.5 and deionized water, ultrasonically dispersing for 30 min, heating to 30° C., adding dopamine hydrochloride and stirring for 8-12 h, centrifuging, washing, and drying to obtain a conductive filler; Further, in step A1, the dosage ratio of Ti3AlC2 powder, hydrofluoric acid, dimethyl sulfoxide and deionized water is 2.5-4.5 g: 40-80 mL: 20 mL: 200 mL; Further, in step A2, the usage ratio of MXene nanosheets, deionized water, sodium hydroxide and chloroacetic acid is 0.5-1.5 g: 100 mL: 9-18 g: 5-12 g; Further, in step A3, the amount ratio of carboxylated MXene nanosheets, DMF, silver nitrate DMF solution, hydrazine hydrate and ethanol is 20-50 g: 100 mL: 100 mL: 40-100 mL: 200 mL; Further, in step A3, the silver nitrate DMF solution is prepared by mixing and stirring silver nitrate and DMF in a dosage ratio of 0.003-0.01 mol:100 mL; Furthermore, in step A4, the usage ratio of MXene / Ag composite material, Tris-HCl buffer, deionized water and dopamine hydrochloride is 1-3 g: 3-5 mL: 100 mL: 0.3-0.6 g.

[0006] The modified polyurethane resin is prepared by the following steps: Step B1, vacuum dehydrating polypropylene glycol (molecular weight of 1000) and 2,2-dihydroxymethylbutyric acid at 100° C. for 2-4 hours, adding 1,4-butanediol, passing nitrogen for 30 minutes, slowly adding isophorone diisocyanate, stirring at 100-120° C. for 1-2 hours, adding dibutyltin dilaurate, and continuing the reaction for 40-60 minutes to obtain a polyurethane prepolymer; Step B2, adding γ-glycidyloxypropyltrimethoxysilane (KH-560) to the polyurethane prepolymer, heating to 30-40°C and stirring for reaction for 30-60 minutes, then adding methyltrimethoxysilane and deionized water and stirring for reaction for 1-2 hours, then adding triethylamine and acetone and stirring for 30 minutes, and rotary evaporation to obtain a modified polyurethane resin; Further, in step B1, the usage ratio of polypropylene glycol, 2,2-dihydroxymethylbutyric acid, 1,4-butanediol, isophorone diisocyanate and dibutyltin dilaurate is 30-50g: 2-4g: 1.5-3.5g: 25-35g: 0.1-0.3g; Furthermore, in step B2, the added amounts of KH-560, methyltrimethoxysilane, deionized water, triethylamine and acetone are 0.3-1 g: 0.1-0.5 g: 3-5 mL: 1-2 g: 5-10 mL.

[0007] A method for preparing a printed silver paste for a touch screen comprises the following steps: Weigh the raw materials by weight, stir the modified polyurethane resin and the organic solvent at 50-70°C for 1-2h, filter with a 150-250 mesh filter to remove insoluble matter, then add silver powder and conductive filler and stir for 30-50min, then mix and grind with a three-roll grinder to a fineness of 5-10μm to obtain a printing silver paste for touch screens.

[0008] Beneficial effects of the present invention: The silver paste prepared by the present invention is prepared from silver powder, conductive filler, modified polyurethane resin and organic solvent as raw materials; wherein the silver powder and the conductive filler act as conductive phases, which not only make the substrate have excellent conductive properties, but also improve the hardness, adhesion and thermal stability of the silver paste after curing, reduce the amount of silver powder used, and reduce the production cost; the organic silicon introduced into the modified polyurethane resin reduces the viscosity of the polyurethane, improves the fluidity of the silver paste, and makes it easy to manufacture and process.

[0009] In the conductive filler, Ti3AlC2 powder is treated with hydrofluoric acid as an etchant and dimethyl sulfoxide as an intercalant to obtain a few-layer or single-layer MXene nanosheet; the MXene nanosheet is then alkalized, and the -Cl on the chloroacetic acid reacts with the -OH on the nanosheet to produce a carboxylated MXene nanosheet; the active groups on the surface and between the layers of the carboxylated MXene nanosheet are then used to complex Ag. + , and then use hydrazine hydrate to reduce Ag +Ag is formed to obtain a MXene / Ag composite material; finally, a polydopamine film is formed on the surface of the MXene / Ag composite material by self-polymerization of dopamine to obtain a conductive filler. The introduction of conductive fillers can not only improve the conductivity of the silver paste, enhance the mechanical strength and hardness, but also reduce the production cost; using MXene nanosheets with excellent conductivity as the substrate, and utilizing their large specific surface area and lamellar structure, the silver powder in the form of tiny particles in the silver paste can be better connected to form a more continuous and stable conductive network, thereby improving the overall conductivity of the silver paste. At the same time, the nanosheets can also provide additional support structures in the silver paste, enhancing the toughness and tensile strength of the silver paste, thereby improving its mechanical strength; and Ag + After complexing on the surface and between layers of MXene nanosheets and then being reduced to Ag using a reducing agent, the conductivity of MXene nanosheets can be further improved; the coating of the polydopamine film can not only utilize its excellent adhesion to improve the adhesion of the silver paste to the substrate, but also synergize with the nanosheets to improve the thermal stability of the silver paste, so that it can still maintain excellent conductive properties under high temperature conditions.

[0010] In the modified polyurethane resin, polypropylene glycol, 2,2-dihydroxymethylbutyric acid, isophorone diisocyanate and 1,4-butanediol are first used as raw materials to synthesize a polyurethane prepolymer under the action of a catalyst, and then the epoxy group in KH-560 reacts with the isocyanate group in the prepolymer to synthesize a polyurethane containing a siloxane or silanol structure at the end, and then methyltrimethoxysilane is added for condensation to obtain a modified polyurethane resin. The modified polyurethane is used as a bonding phase in the silver paste, has good flexibility and bonding properties, and can make the silver paste have excellent adhesion to the substrate after curing; in addition, the introduction of silicone in the polyurethane can reduce the viscosity of the polyurethane, improve its fluidity in the silver paste, facilitate coating between the glass substrate and the ITO conductive film, and is easy to manufacture and process. It can also improve the durability and reliability of the substrate, so that the substrate can maintain stable performance under long-term use and harsh environments. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Example 1: The conductive filler is prepared by the following steps: Step A1, add 2.5g Ti3AlC2 powder to 40mL, 40% hydrofluoric acid (w / v), and stir in a water bath at 30°C for 8h, filter and wash until the pH of the filtrate is 6, then dry the filter cake, place it in 20mL dimethyl sulfoxide and stir for 8h, centrifuge, wash, redisperse in 200mL deionized water, ultrasonically treat for 3h, centrifuge, and freeze-dry to obtain MXene nanosheets; Step A2, 0.5 g of MXene nanosheets were evenly dispersed in 100 mL of deionized water, 6 g of sodium hydroxide was added and stirred for 1.5 h, and then 5 g of chloroacetic acid and 3 g of sodium hydroxide were added, and the temperature was raised to 55 ° C and stirred for 2 h, washed to neutrality, and dried to obtain carboxylated MXene nanosheets; Step A3, 20g of carboxylated MXene nanosheets were evenly dispersed in 100mL of N,N-dimethylformamide (DMF), 100mL of silver nitrate DMF solution was slowly added dropwise, stirred evenly, the pH of the system was adjusted to 10, and then 40mL of 80wt% hydrazine hydrate was added, reacted at 35°C for 30min, filtered, washed, redispersed in 200mL of ethanol and stirred for 1h, filtered, and dried to obtain a MXene / Ag composite material. The silver nitrate DMF solution was prepared by mixing and stirring silver nitrate and DMF in a dosage ratio of 0.003mol:100mL; Step A4, disperse 1 g of MXene / Ag composite material in a mixture of 3 mL, 0.5 mol / L, pH 8.5 Tris-HCl buffer and 100 mL of deionized water, ultrasonically disperse for 30 min, heat to 30 ° C, add 0.3 g of dopamine hydrochloride and stir for 8 h, centrifuge, wash and dry to obtain a conductive filler.

[0013] The modified polyurethane resin is prepared by the following steps: Step B1, 30g of polypropylene glycol (molecular weight of 1000) and 2g of 2,2-dimethylolbutyric acid were vacuum dehydrated at 100°C for 2h, 1.5g of 1,4-butanediol was added, nitrogen was introduced for 30min, 25g of isophorone diisocyanate was slowly added, the mixture was stirred at 100°C for 1h, 0.1g of dibutyltin dilaurate was added, and the reaction was continued for 40min to obtain a polyurethane prepolymer; Step B2: add 0.3 g of γ-glycidyloxypropyltrimethoxysilane (KH-560) to the polyurethane prepolymer, heat to 30 °C and stir to react for 30 min, then add 0.1 g of methyltrimethoxysilane and 3 mL of deionized water and stir to react for 1 h, then add 1 g of triethylamine and 5 mL of acetone and stir for 30 min, and rotary evaporate to obtain the modified polyurethane resin.

[0014] Example 2: The conductive filler is prepared by the following steps: Step A1, add 3.5g Ti3AlC2 powder to 60mL, 40% hydrofluoric acid (w / v), and stir in a water bath at 35°C for 9h, filter and wash until the pH of the filtrate is 6.5, then dry the filter cake, place it in 20mL dimethyl sulfoxide and stir for 10h, centrifuge, wash, redisperse in 200mL deionized water, ultrasonically treat for 4.5h, centrifuge, and freeze-dry to obtain MXene nanosheets; Step A2, disperse 1 g of MXene nanosheets evenly in 100 mL of deionized water, add 9 g of sodium hydroxide and stir for 2 h, then add 9 g of chloroacetic acid and 4.5 g of sodium hydroxide, heat to 60 ° C and stir for 3 h, wash to neutrality, and dry to obtain carboxylated MXene nanosheets; Step A3, 35g of carboxylated MXene nanosheets were evenly dispersed in 100mL of N,N-dimethylformamide (DMF), 100mL of silver nitrate DMF solution was slowly added dropwise, stirred evenly, the pH of the system was adjusted to 10.5, and then 70mL of 80wt% hydrazine hydrate was added, reacted at 40°C for 45min, filtered, washed, redispersed in 200mL of ethanol and stirred for 1.5h, filtered, and dried to obtain a MXene / Ag composite material. The silver nitrate DMF solution was prepared by mixing and stirring silver nitrate and DMF in a dosage ratio of 0.006mol:100mL; Step A4, disperse 2 g of MXene / Ag composite material in a mixture of 4.5 mL, 0.5 mol / L, pH 8.5 Tris-HCl buffer and 100 mL of deionized water, ultrasonically disperse for 30 min, heat to 30 ° C, add 0.45 g of dopamine hydrochloride and stir for 10 h, centrifuge, wash and dry to obtain a conductive filler.

[0015] The modified polyurethane resin is prepared by the following steps: Step B1, 40g of polypropylene glycol (molecular weight of 1000) and 3g of 2,2-dimethylolbutyric acid were vacuum dehydrated at 100°C for 3h, 2.5g of 1,4-butanediol was added, nitrogen was introduced for 30min, 30g of isophorone diisocyanate was slowly added, the mixture was stirred at 110°C for 1.5h, 0.2g of dibutyltin dilaurate was added, and the reaction was continued for 50min to obtain a polyurethane prepolymer; Step B2: add 0.6 g of γ-glycidyloxypropyltrimethoxysilane (KH-560) to the polyurethane prepolymer, heat to 35 °C and stir to react for 45 min, then add 0.3 g of methyltrimethoxysilane and 4 mL of deionized water and stir to react for 1.5 h, then add 1.5 g of triethylamine and 7 mL of acetone and stir for 30 min, and rotary evaporate to obtain the modified polyurethane resin.

[0016] Example 3: The conductive filler is prepared by the following steps: Step A1, add 4.5g Ti3AlC2 powder to 80mL, 40% hydrofluoric acid (w / v), and stir in a 40°C water bath for 10h, filter and wash until the pH of the filtrate is 7, then dry the filter cake, place it in 20mL dimethyl sulfoxide and stir for 12h, centrifuge, wash, redisperse in 200mL deionized water, ultrasonically treat for 5h, centrifuge, and freeze-dry to obtain MXene nanosheets; Step A2, 1.5 g of MXene nanosheets were evenly dispersed in 100 mL of deionized water, 12 g of sodium hydroxide was added and stirred for 2.5 h, then 12 g of chloroacetic acid and 6 g of sodium hydroxide were added, and the temperature was raised to 65 ° C and stirred for 4 h, washed to neutrality, and dried to obtain carboxylated MXene nanosheets; Step A3, 50g of carboxylated MXene nanosheets were evenly dispersed in 100mL of N,N-dimethylformamide (DMF), 100mL of silver nitrate DMF solution was slowly added dropwise, stirred evenly, the pH of the system was adjusted to 11, and then 100mL of 80wt% hydrazine hydrate was added, reacted at 45°C for 50min, filtered, washed, redispersed in 200mL of ethanol and stirred for 2h, filtered, and dried to obtain a MXene / Ag composite material. The silver nitrate DMF solution was prepared by mixing and stirring silver nitrate and DMF in a dosage ratio of 0.01mol:100mL; Step A4, disperse 3 g of MXene / Ag composite material in a mixture of 5 mL, 0.5 mol / L, pH 8.5 Tris-HCl buffer and 100 mL of deionized water, ultrasonically disperse for 30 min, heat to 30 ° C, add 0.6 g of dopamine hydrochloride and stir for 12 h, centrifuge, wash, and dry to obtain a conductive filler.

[0017] The modified polyurethane resin is prepared by the following steps: Step B1, 50g of polypropylene glycol (molecular weight of 1000) and 4g of 2,2-dimethylolbutyric acid were vacuum dehydrated at 100°C for 4h, 3.5g of 1,4-butanediol was added, nitrogen was introduced for 30min, 35g of isophorone diisocyanate was slowly added, stirred at 120°C for 2h, 0.3g of dibutyltin dilaurate was added, and the reaction was continued for 60min to obtain a polyurethane prepolymer; Step B2: add 1 g of γ-glycidyloxypropyltrimethoxysilane (KH-560) to the polyurethane prepolymer, heat to 40°C and stir to react for 60 min, then add 0.5 g of methyltrimethoxysilane and 5 mL of deionized water and stir to react for 2 h, then add 2 g of triethylamine and 10 mL of acetone and stir for 30 min, and rotary evaporate to obtain the modified polyurethane resin.

[0018] Embodiment 4: A method for preparing a printed silver paste for a touch screen comprises the following steps: 45 parts of silver powder, 10 parts of the conductive filler prepared in Example 1, 8 parts of the modified polyurethane resin prepared in Example 1, and 20 parts of tributyl citrate; The raw materials were weighed by weight, and the modified polyurethane resin prepared in Example 1 and tributyl citrate were stirred at 50° C. for 1 h. The insoluble matter was filtered out with a 150-mesh filter, and then silver powder and the conductive filler prepared in Example 1 were added and stirred for 30 min. The mixture was then fully mixed and ground with a three-roll grinder to a fineness of 5 μm to obtain a printed silver paste for a touch screen.

[0019] Embodiment 5: A method for preparing a printed silver paste for a touch screen comprises the following steps: 55 parts of silver powder, 15 parts of the conductive filler prepared in Example 2, 11 parts of the modified polyurethane resin prepared in Example 2, and 25 parts of butyl butyrate; The raw materials were weighed by weight, and the modified polyurethane resin prepared in Example 2 and butyl butyrate were stirred at 60° C. for 1.5 h, and the insoluble matter was filtered out with a 200-mesh filter. Silver powder and the conductive filler prepared in Example 2 were added and stirred for 40 min, and then the mixture was fully mixed and finely ground with a three-roll grinder to a fineness of 7 μm to obtain a printing silver paste for a touch screen.

[0020] Embodiment 6: A method for preparing a printed silver paste for a touch screen comprises the following steps: 65 parts of silver powder, 20 parts of the conductive filler prepared in Example 3, 15 parts of the modified polyurethane resin prepared in Example 3, and 30 parts of diethyl glutarate; The raw materials were weighed by weight, and the modified polyurethane resin prepared in Example 3 and diethyl glutarate were stirred at 70° C. for 2 h, and the insoluble matter was filtered out with a 250-mesh filter. Silver powder and the conductive filler prepared in Example 3 were added and stirred for 50 min, and then the mixture was fully mixed and finely ground with a three-roll grinder to a fineness of 10 μm to obtain a printed silver paste for a touch screen.

[0021] Comparative Example 1: This comparative example is a printing silver paste, which differs from Example 6 in that conductive graphite is used instead of the conductive filler prepared in Example 3, and the rest are the same.

[0022] Comparative Example 2: This comparative example is a printing silver paste. The difference from Example 6 is that polyurethane resin is used instead of the modified polyurethane resin prepared in Example 3, and the rest is the same.

[0023] Performance test: The pastes prepared in Examples 4-6 and Comparative Examples 1-2 were printed on ITO / PET film and ITO / glass using a 325-mesh stainless steel screen. The printed film thickness was 10 μm. The ITO glass was cured at 150° C. for 45 min. The cured film thickness was 8 μm. The performance of the conductive silver paste cured film was tested. Test method: The square resistance of the silver paste cured film is determined according to the provisions of GB / T 17473.3. The printed pattern is 0.6mm×60mm, and the resistance and thickness of the cured film are measured and converted; at the same time, it is placed under 70℃, 90%RH temperature and humidity conditions for 240h, and the change rate of the square resistance is measured; the hardness of the silver paste cured film is determined according to the provisions of GB / T 6739 and measured by a pencil hardness tester; the adhesion of the silver paste cured film is tested by a hundred grid test, and after the hundred grid knife is scratched, the 3M#600 tape is peeled off for testing.

[0024] The test results are shown in Table 1:

[0025] As can be seen from Table 1, the printed silver paste prepared by the present invention has the advantages of excellent bonding performance, adhesion, high hardness and good conductivity, and therefore, using it in the manufacture of touch screens has a good application prospect and reduces the production cost.

[0026] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A printing silver paste for a touch screen, characterized in that: The invention comprises the following raw materials in parts by weight: 45-65 parts of silver powder, 10-20 parts of conductive filler, 8-15 parts of modified polyurethane resin, and 20-30 parts of organic solvent; The conductive filler is prepared by the following steps: Step A1, add 40% hydrofluoric acid to Ti3AlC2 powder, stir in a water bath at 30-40°C for 8-10 hours, filter and wash until the pH of the filtrate is 6-7, then dry the filter cake, stir in dimethyl sulfoxide for 8-12 hours, centrifuge, wash, redisperse in deionized water for ultrasonic treatment for 3-5 hours, centrifuge, and freeze-dry to obtain MXene nanosheets; Step A2, disperse the MXene nanosheets evenly in deionized water, add 2 / 3 of the mass of sodium hydroxide and stir for 1.5-2.5 hours, then add chloroacetic acid and the remaining sodium hydroxide, heat to 55-65°C and stir for 2-4 hours, wash to neutrality, and dry to obtain carboxylated MXene nanosheets; Step A3, disperse the carboxylated MXene nanosheets evenly in N,N-dimethylformamide, slowly drop the silver nitrate DMF solution, stir evenly, adjust the pH of the system to 10-11, then add 80wt% hydrazine hydrate, react at 35-45°C for 30-50min, filter, wash, redisperse in ethanol and stir for 1-2h, filter, and dry to obtain a MXene / Ag composite material; Step A4, disperse the MXene / Ag composite material in a mixture of 0.5 mol / L Tris-HCl buffer with a pH of 8.5 and deionized water, ultrasonically disperse for 30 minutes, heat to 30°C, add dopamine hydrochloride and stir for 8-12 hours, centrifuge, wash and dry to obtain a conductive filler.

2. A printing silver paste for touch screen according to claim 1, characterized in that: In step A1, the dosage ratio of Ti3AlC2 powder, hydrofluoric acid, dimethyl sulfoxide and deionized water is 2.5-4.5 g: 40-80 mL: 20 mL: 200 mL.

3. The printing silver paste for touch screen according to claim 1, characterized in that: In step A2, the dosage ratio of MXene nanosheets, deionized water, sodium hydroxide and chloroacetic acid is 0.5-1.5 g: 100 mL: 9-18 g: 5-12 g.

4. The printing silver paste for touch screen according to claim 1, characterized in that: In step A3, the amount ratio of carboxylated MXene nanosheets, DMF, silver nitrate DMF solution, hydrazine hydrate and ethanol is 20-50 g: 100 mL: 100 mL: 40-100 mL: 200 mL, and the silver nitrate DMF solution is prepared by mixing and stirring silver nitrate and DMF in an amount ratio of 0.003-0.01 mol: 100 mL.

5. The printing silver paste for touch screen according to claim 1, characterized in that: In step A4, the usage ratio of MXene / Ag composite material, Tris-HCl buffer, deionized water and dopamine hydrochloride is 1-3 g: 3-5 mL: 100 mL: 0.3-0.6 g.

6. The printing silver paste for touch screen according to claim 1, characterized in that: The organic solvent is one or two of butyl butyrate, diethyl glutarate and tributyl citrate.

7. The printing silver paste for touch screen according to claim 1, characterized in that: The modified polyurethane resin is prepared by the following steps: Step B1, vacuum dehydrating polypropylene glycol and 2,2-dihydroxymethylbutyric acid at 100° C. for 2-4 hours, adding 1,4-butanediol, introducing nitrogen for 30 minutes, slowly adding isophorone diisocyanate, stirring at 100-120° C. for 1-2 hours, adding dibutyltin dilaurate, and continuing the reaction for 40-60 minutes to obtain a polyurethane prepolymer; Step B2, add γ-glycidyloxypropyltrimethoxysilane to the polyurethane prepolymer, heat to 30-40°C and stir to react for 30-60 minutes, then add methyltrimethoxysilane and deionized water and stir to react for 1-2 hours, then add triethylamine and acetone and stir for 30 minutes, and rotary evaporate to obtain a modified polyurethane resin.

8. The printing silver paste for touch screen according to claim 7, characterized in that: In step B1, the usage ratio of polypropylene glycol, 2,2-dihydroxymethylbutyric acid, 1,4-butanediol, isophorone diisocyanate and dibutyltin dilaurate is 30-50g: 2-4g: 1.5-3.5g: 25-35g: 0.1-0.3g.

9. The printing silver paste for touch screen according to claim 7, characterized in that: In step B2, the added amounts of KH-560, methyltrimethoxysilane, deionized water, triethylamine and acetone are 0.3-1 g: 0.1-0.5 g: 3-5 mL: 1-2 g: 5-10 mL.

10. A method for preparing a printing silver paste for a touch screen according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh the raw materials by weight, stir the modified polyurethane resin and the organic solvent at 50-70°C for 1-2h, filter with a 150-250 mesh filter to remove insoluble matter, then add silver powder and conductive filler and stir for 30-50min, then mix and grind with a three-roll grinder to a fineness of 5-10μm to obtain a printing silver paste for touch screens.

Citation Information

Patent Citations

  • Conductive silver paste for fine line silk-screen printing for capacitive type touch screen

    CN105788702A

  • Touch screen silver paste and preparation method thereof

    CN106683747A

  • Preparation method of MXene and application of MXene as reinforcement phase of conductive silver paste

    CN111863310A

  • Preparation method and application of Ti3C2Tx-Mxene poly-dopamine-nano-silver composite material

    CN117304575A

  • High-fitting-degree composite packaging paper, preparation process thereof and application of high-fitting-degree composite packaging paper in irregular products

    CN117684417A

Cited By

  • Spherical nano silver powder and preparation method thereof

    CN120961907A

  • Spherical silver nanopowder and method for preparing the same

    CN120961907B

  • Low-temperature fast-curing silver paste for FPC antenna and preparation method of low-temperature fast-curing silver paste

    CN121687613A